Attrition of a creole : the syntactic effects of the L2 acquisition of papiamentu on Jamaican creole - Messam-Johnson, Trecel Jannel (My University, 2022)
This study investigates the attrition of Jamaican Creole (JC), in a Papiamentu (Pp) dominant environment, to determine the syntactic features of JC first language (L1) attrition, a projected timeline during which each feature may fall prey to attrition and the degree to which features of the grammar may be affected. No known research on the attrition of Creole languages has previously been done. Five data types were collected from 20 informants, who shared a similar sociolinguistic profile and who had been residing in Curaçao for periods between 1 and 21 years. These data were collected via natural use, clinical elicitation, experimental elicitation, metalinguistic judgements and self-report data. The data were analysed to determine recurring deviations that were common to informants who were placed in three categories according to their years of residence in the second language (L2) country: 1-5 years, 6-10 years and >10 years. Recurring deviations were identified at the level of the Determiner Phrase (DP), the Verb Phrase (VP) and the Sentence. Changes in the grammar were found to result from cross-linguistic influence. In addition, there were ‘internally induced’ changes, that is, changes that could not be attributed to influence from an L2. It was also found that changes in the affected L1 could become apparent after one year of contact and that most changes in the attriting grammar occurred within the first 5 years of migration. Implications of this study include the following: in an effort to maintain native speaker functionality in the L1, and in formal L1 instruction, emphasis should be on features found to be susceptible to language attrition; priority ought to be given to those features which have proven to be most susceptible to change; given that the majority of stable changes take place within the first 5 years of contact, to achieve optimum success, maintenance efforts should be most intense during these early years; and finally, success at maintenance may be less likely after 10 years of contact as the majority of changes were found to have occurred by then
Keywords: Language attrition -- Curacao; Papiamento -- Foreign elements -- English; Creole dialects, Jamaican; English language -- Dialects -- Jamaica; Language transfer (Language learning); Second language acquisition; Language maintenance; Interlanguage (Language learning) -- Curacao